Two modes of amnesia: complexity in postcolonial Namibia - Kössler, Reinhart (University of the Free State, 2015)
Public commemoration of past atrocity, mass crime and particularly genocide has drawn attention both in the public realm and in scholarly debate, meeting general acceptance in recent years. However, the seeming opposite has also been advocated – forgetting. Variously, such forgetting is presented as a wiser approach in contradistinction to painstaking and evasive truth-seeking. Taking this tendency as a point of departure, I discuss here two cases that seem relevant to what might be called a strategy of amnesia, both relating to Namibia: (1) reference to the genocide perpetrated by the German colonial army in 1904-08, both in post-World War II (West) Germany and in the independent postcolony, and (2) the debates and conflicts within Namibia around the gross violations of human rights committed under the auspices of SWAPO during the 1980s. Without suggesting that these cases are in any way equivalent, I contend, however, that they are related in the minds of a fair number of Namibians and further, that there are certain connections in the ways both cases have been and are addressed within the public spheres of the two countries concerned. I argue that in both cases, debate on how to ‘work through’ or otherwise pass over in silence violent acts and large-scale crime arose only with the Namibian independence process in 1989/90. In the first case, we can observe a transnational dynamic, which has resulted in shifts in the positioning of both governments concerned, but at the same time refers back to more long-term official images of history. This concerns in particular the construction of national identity as a decisive framing of the transition process, which, in Namibia, was intertwined with achieving independence. In the German case as well, memory politics are closely related to transition to democracy, even though this transition was the result of the cataclysmic defeat of Nazism. In such contexts, strategies of amnesia or of repressing memory appear fragile in face of the ever-present possibility that interested or concerned actors may raise seemingly forgotten issues. Precisely because of their relative volubility, such strategies also pose questions about political culture. In a closing section, I therefore consider the societal power relations that influence the prospects of enduring amnesia in the cases discussed.
Keywords: Genocide; Forgetting; Human rights abuses; Namibia